2020
DOI: 10.1371/journal.pone.0239333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking on tuberculosis treatment outcomes: A systematic review and meta-analysis

Abstract: Introduction Numerous studies have explored an effect of cigarette smoking on tuberculosis treatment outcomes but with dissimilar conclusions. Objective To determine the effect of cigarette smoking on tuberculosis treatment outcomes. Methods PubMed, Cochrane library and Google scholar databases were searched last on February 27, 2019. We applied the random-effects model for the analysis. Publication bias was assessed using funnel plot and Egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 47 publications
(264 reference statements)
0
29
1
2
Order By: Relevance
“…We found that few host factors were associated with LTBI status. In contrast, the elderly had a higher prevalence of birth cohort characteristics that are known risk factors for active TB in adults, such as diabetes and lower education [31,32]. Interestingly, despite the high prevalence of diabetes in the elderly population, we found that it was not associated with TB.…”
Section: Discussioncontrasting
confidence: 74%
“…We found that few host factors were associated with LTBI status. In contrast, the elderly had a higher prevalence of birth cohort characteristics that are known risk factors for active TB in adults, such as diabetes and lower education [31,32]. Interestingly, despite the high prevalence of diabetes in the elderly population, we found that it was not associated with TB.…”
Section: Discussioncontrasting
confidence: 74%
“…A study showed that when developing policies and actions aimed at abstinence from smoking among patients diagnosed with TB, there was a decrease in the rate of diagnoses and deaths after smoking cessation [31]. Thus, after six weeks of smoking cessation, the adverse effects of tobacco on the immune system disappear and contribute to a better clinical evolution of the patient [32].…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Patients with poor TB treatment outcomes were 50% more exposed to smoking than patients with successful treatment. [ 16 ] Smokers are less likely to adhere to TB treatment and more likely to relapse after successfully completing treatment. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%